Preparation method of high-entropy carbide-based metal ceramic

4-5 transition group metal carbides were ground to the nanoscale by a two-step ball milling method and mixed with metal binder, which solved the problem of high entropy carbide powder synthesis temperature leading to coarse grains, and a high entropy carbide-based metal cermet with high mechanical properties was successfully prepared.

CN119506638AActive Publication Date: 2025-02-25JIANGXI MINGRUI SPECIAL ALLOY CO LTD

Patent Information

Application Number
CN202411771969.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-25
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

It is difficult to prepare high-entropy carbide-based metal cermets with uniform phase, high density and small grains, and high entropy carbide powder synthesis temperature is high and it is easy to produce powder particles with large grains, affecting the mechanical properties of the ceramics.

Method used

Using a two-step ball milling method, high-energy ball milling is performed by a sand mill, 4-5 types of transition group metal carbides are ground to nano-level, and then mixed with metal binders and the second ball milling is performed to form a highly sintering activity carbide-based metal cermet composite powder. High entropy carbide-based metal cermet can be obtained after spray drying, press forming and sintering.

Benefits of technology

The high entropy carbide-based cermet obtained by the two-step ball milling method has the characteristics of small grains and high mechanical properties. It has a bending strength of better than 2100MPa, a fracture toughness of better than 8.5 MPa·m0.5, and a Rockwell hardness of better than 92.0. It is suitable for bearing materials, cutting tools, mold materials and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506638A_ABST
    Figure CN119506638A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of high-entropy carbide-based metal ceramic, which comprises the following steps: step 1, preparing according to the molar ratio of a carbide addition phase, putting powder into a sand mill, and carrying out first ball milling; 2, carrying out secondary ball milling, adding a metal binder, carbon black, paraffin, rubber or polyvinyl alcohol and other binders into the mixed carbide powder, carrying out ball milling, mixing, and carrying out spray drying on the mixed powder after the ball milling is finished; thirdly, the powder is subjected to pressing forming, and the pressing pressure ranges from 50 MPa to 200 MPa; and fourthly, the pressed blank is degreased and sintered, and the high-entropy carbide-based metal ceramic is obtained. The high-entropy carbide-based metal ceramic material with the bending strength superior to 2100 MPa, the fracture toughness superior to 8.5 MPa.m < 0.5 > and the Rockwell hardness superior to 92.0 can be obtained, and the high-entropy carbide-based metal ceramic material can be widely applied to the fields of bearing materials, cutting tools, mold materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal ceramics, and in particular to a method for preparing high entropy carbide-based metal ceramics. Background Art

[0002] Transition metal carbides, such as TiC, WC, and Mo2C, have high red hardness, high strength, and excellent wear resistance. They are the main wear-resistant components of high-speed cutting tools and hot-working die materials for metal processing such as steel. At present, transition metal carbides composed of 4-5 equal (nearly equal) molar metal atomic ratios have become a research hotspot, such as (TiWMoVNb)C, (TaZrNbWMo)C, etc. Due to the characteristics of high entropy values, this type of high entropy carbide has a more stable phase structure than conventional transition metal carbides, and thus exhibits excellent chemical stability, high red hardness, wear resistance, etc., becoming a potential candidate material for the new generation of metal ceramics. Based on this, the development of a metal ceramic with high entropy carbide as the main ceramic component and bonded by a metal bonding phase such as iron, cobalt, and nickel has great performance potential and application value.

[0003] However, it is currently very challenging to obtain high-entropy carbide-based cermets with uniform phase, high density and fine grains. The main reasons are as follows: 1. The preparation of high-entropy carbide ceramic powder raw materials is still immature. Although there are many chemical synthesis methods such as co-precipitation to achieve it, it is difficult to mass produce and the cost is high; 2. If multiple components are mixed and then calcined to prepare high-entropy carbide powder, the calcination temperature is relatively high (up to 1900-2000℃) to achieve uniform diffusion between multiple components, which will cause the generated high-entropy carbide powder to have coarse grains, reducing the mechanical properties of the cermet.

[0004] In order to obtain high-performance high-entropy metal ceramics with fine grains and single phase, the high-entropy metal ceramics in the prior art need to obtain ultrafine high-entropy carbide ceramic powder with high sintering activity. Therefore, there are mainly the following two problems.

[0005] Question 1: Ultra-high activity high entropy carbide ceramic powder needs to have a powder particle size of micro-nano level, such as less than 0.5 microns. However, the synthesis temperature of high entropy carbide powder is high (uniform diffusion is required to form a high entropy ceramic single phase), which easily produces powder particles with larger grains. At the same time, if chemical synthesis is adopted, although ultra-fine high entropy ceramic powder can be synthesized using precursors, this method is not suitable for industrial mass production.

[0006] Question 2: High-entropy carbides are difficult to form high-entropy phases and require very high carbonization temperatures, which will result in coarse grains of high-entropy metal-ceramics and mechanical properties that are difficult to match those of conventional metal-ceramics. Summary of the invention

[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a high entropy carbide-based cermet.

[0008] In order to achieve the above object, a method for preparing a high entropy carbide-based cermet comprises the following steps: Step 1: According to the molar ratio of the carbide additive phase, the powder is prepared and placed in a sand mill for the first ball milling. The ball-to-material ratio is 10-15:1, the ball milling time is 2-5 hours, the ball milling speed is 50-100r / min, and the grinding medium is anhydrous ethanol. The powder after high-energy grinding is then vacuum dried. After drying, it is vacuum packaged and stored; Step 2: Perform a second ball milling, add metal binder, carbon black, paraffin, rubber or polyvinyl alcohol and other binders to the mixed carbide powder, and then perform ball milling. The ball milling medium is anhydrous ethanol, the ball-to-material ratio is 5:1-8:1, the ball milling time is 24-48h, and the ball milling speed is 80-120r / min. After the ball milling, the mixed powder is spray dried at a drying temperature of 50-80°C, and the particle size of the mixed powder is 20-50 microns; Step 3, pressing the powder into a shape with a pressing pressure of 50-200 MPa; Step 4, the green sheet is degreased and sintered to obtain a high entropy carbide-based cermet; the sintering is vacuum sintering or atmosphere pressure sintering, and if vacuum sintering is performed, the vacuum degree is 5-50Pa; if it is atmosphere pressure sintering, the protective gas is argon, and the gas pressure is 0.5-5MPa; the sintering temperature is 1400-1500°C, and the sintering time is 1-3h.

[0009] Preferably, in step one, the carbide is commercial carbide powder, which is composed of at least 4-6 transition metal carbides of TiC, WC, Mo2C, TaC, NbC, ZrC, VC, HfC and Cr2C3; the molar ratio of the metal elements of each added phase is 0.8-1:1-1.2, the ratio difference is ≤20wt%, and the metal bonding phase used is at least one of iron, cobalt and nickel.

[0010] Preferably, the 4 to 6 transition metal carbides contain at least two phases of TiC and WC.

[0011] Preferably, in step 1, the carbide additive phase can be added in the form of single carbide powder or solid solution powder.

[0012] Preferably, in step 1, the molar ratio of the metal elements of each added phase of the carbide is 0.9-1:1-1.1.

[0013] Preferably, the average particle size of the commercial carbide powder is 0.5-5.0 microns, the average particle size of the binder phase powder is 1.0-3.0 microns, and the average particle size of the carbon black is 0.1-2.0 microns.

[0014] Preferably, in step 2, the content of the metal binder is 15-25wt%, the mass fraction of the carbon black accounts for 0.8-2.0% of the total powder, and the content of the binder such as paraffin, rubber or polyvinyl alcohol accounts for 1.0-3.0wt% of the mass of the metal ceramic powder. Preferably, in step 2, the carbon black is one of colloidal graphite and pyrolytic carbon black.

[0015] Preferably, in step 4, the degreasing is carried out in a vacuum environment, the degreasing temperature is 300-500° C., and the degreasing time is 2-5 hours.

[0016] Preferably, in step 4, the sintering process is to first raise the temperature to 1000-1200° C. in a vacuum environment, keep the temperature for 1-3 hours, and then perform vacuum sintering, or introduce argon gas for pressure sintering.

[0017] By using a sand mill to perform high-energy ball milling on 4-5 transition metal carbides, the obtained mixed powder has reached a near-nanoscale mixing level. Although no single high-entropy carbide component is formed, it has high sintering activity and can easily form a high-entropy carbide single phase in the subsequent sintering process. The sintering temperature is low, and a high-entropy carbide-based metal ceramic with fine grains can be formed.

[0018] Through a two-step ball milling method, a carbide-based metal-ceramic composite powder with high sintering activity is obtained. After subsequent liquid phase sintering, a high-entropy carbide-based metal-ceramic material with fine grains and high mechanical properties can be obtained.

[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention cleverly utilizes the ball milling method twice, that is, the first time, 4-5 kinds of transition metal carbides are ground to the nanometer level by high-energy ball milling combined with the grinding efficiency of a sand mill; the second time, the mixed transition metal carbide powder is evenly mixed with the binding phase iron, cobalt, nickel, etc., and then sintered to obtain a high entropy carbide-based metal ceramic.

[0020] 2. The sand mill improves the sintering activity of metal ceramic nanopowders, but the adsorbed oxygen content on its surface is significantly higher than that of conventional mixed powders. Therefore, the present invention ensures the preparation of high sintering activity and high entropy carbide-based metal ceramics by adjusting the addition of carbon content and performing negative pressure insulation at the deoxidation temperature.

[0021] 3. The present invention can obtain a bending strength better than 2100 MPa and a fracture toughness better than 8.5 MPa·m0.5 The high-entropy carbide-based cermet material with a Rockwell hardness better than 92.0 can be widely used in bearing materials, cutting tools, mold materials and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0023] Figure 1 The present invention is a flow chart of a preparation method of a high entropy carbide-based cermet.

[0024] Figure 2 This is the morphology of the high entropy carbide ceramic powder after the first step of ball milling in Example 1 of the present invention. After ball milling, the particle size of the multi-component metal ceramic carbide powder is about 200 nm.

[0025] Figure 3 This is the microscopic morphology of the high entropy metal ceramic in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0027] like Figure 1-Figure 3 As shown, the composition is: 83.5(W, Ta, Ti, Nb, Zr)C-15Ni-1.5C metal ceramic, where the atomic ratio of W:Ta:Ti:Nb:Zr is 1.0:1:1.1:0.9:1.0.

[0028] The mass fraction of the metal ceramic component is 83.5 parts of high entropy carbide ceramic powder, 15 parts of a binder phase and 1.5 parts of pyrolytic carbon black. The high entropy carbide powder is added in the form of single-phase WC, TaC, TiC, NbC and ZrC, and the average particle sizes of the above powders are 0.8, 1.2, 1.5, 0.5 and 1.0 microns, respectively, the particle size of the nickel powder is 1.0 micron, and the particle size of the carbon black is 0.2 micron.

[0029] The preparation steps of the high entropy carbide-based cermet are as follows: (1) the first ball milling is performed, and the powder is prepared according to the molar ratio of the carbide additive phase, and the powder is placed in a sand mill, the ball-to-material ratio is 12:1, the ball milling time is 3 hours, the ball milling speed is 60r / min, and the grinding medium is anhydrous ethanol. Subsequently, the powder after high-energy grinding is vacuum dried, and after drying, it is vacuum packaged and stored; (2) the second ball milling is performed, and the mixed carbide powder is added with nickel powder and carbon black; paraffin wax accounting for 2wt% of the mass fraction of the above powder is added as a forming agent, and then ball milling is performed, the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 8:1, the ball milling time is 36 hours, and the ball milling speed is 100r / min. After ball milling, the mixed powder is spray dried at a drying temperature of 60°C and a particle size of 20 microns; (3) the powder is pressed into a shape at a pressing pressure of 80 MPa; (4) the pressed green body is degreased and sintered to obtain a high entropy carbide-based metal ceramic; the degreasing is carried out in a vacuum environment at a degreasing temperature of 450°C and a degreasing time of 2 hours; the sintering is vacuum sintering at a vacuum degree of 10 Pa; first, the temperature is raised to 1100°C in a vacuum environment and kept at this temperature for 2 hours, and then vacuum sintering is carried out at a sintering temperature of 1450°C and kept at this temperature for 2 hours to obtain a high entropy carbide-based metal ceramic material.

[0030] The high entropy carbide ceramic grain size is 2.5 microns, its porosity reaches A04B00C00 level, its bending strength is 2100MPa, and its fracture toughness is 8.5MPa·m 0.5 , Rockwell hardness is 93.2 HRA, and it is a metal ceramic tooling material with wide application potential.

[0031] like Figure 1 As shown, the composition is: 79(W, Mo,Ti, V, Zr)C-20Co-1.0C metal ceramic, wherein the atomic ratio of W: Mo:Ti:V:Zr = 1:0.9:1.0:1.0:0.8.

[0032] The mass fraction of the metal ceramic component is 79 parts of high entropy carbide ceramic powder, 20 parts of bonding phase and 1.0 parts of pyrolytic carbon black. The high entropy carbide powder is added in the form of single-phase WC, Mo2C, TiC, VC, and ZrC, and the average particle sizes of the above powders are 1.5, 1.0, 1.2, 0.8, and 1.8 microns, respectively, the particle size of the cobalt powder is 1.0 micron, and the particle size of the carbon black is 0.2 micron.

[0033] The preparation steps of the high entropy carbide-based cermet are as follows: (1) the first ball milling is performed, and the powder is prepared according to the molar ratio of the carbide additive phase, and the powder is placed in a sand mill, the ball-to-material ratio is 10:1, the ball milling time is 2 hours, the ball milling speed is 60r / min, and the grinding medium is anhydrous ethanol. Subsequently, the powder after high-energy grinding is vacuum dried, and after drying, it is vacuum packaged and stored; (2) the second ball milling is performed, and the mixed carbide powder is added with cobalt powder and carbon black; paraffin wax accounting for 2wt% of the mass fraction of the above powder is added as a forming agent, and then ball milling is performed, the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 6:1, the ball milling time is 24 hours, and the ball milling speed is 100r / min. After ball milling, the mixed powder is spray dried at a drying temperature of 60°C and a particle size of 30 microns; (3) the powder is pressed into a shape at a pressing pressure of 100 MPa; (4) the pressed green body is degreased and sintered to obtain a high entropy carbide-based metal ceramic; the degreasing is carried out in a vacuum environment at a degreasing temperature of 450°C and a degreasing time of 2 hours; the sintering is vacuum sintering at a vacuum degree of 10 Pa; first, the temperature is raised to 1100°C in a vacuum environment and kept at this temperature for 2 hours, and then vacuum sintering is carried out at a sintering temperature of 1450°C and kept at this temperature for 2 hours to obtain a high entropy carbide-based metal ceramic material.

[0034] The grain size of the high entropy carbide ceramic is 1.5 microns, its porosity reaches the A04B00C00 level, its bending strength is 2240MPa, and its fracture toughness is 9.0MPa·m 0.5 , Rockwell hardness is 92.8 HRA, and it is a metal ceramic tooling material with wide application potential.

[0035] like Figure 1 As shown, the composition is: 74.2(W, Nb, Ti, V, Cr)C-15Fe-10Co-0.8C metal ceramic, where the atomic ratio of W:Nb:Ti:V:Cr is 1:0.9:1.0:1.0:0.8.

[0036] The mass fraction of the metal ceramic component is 74.2 parts of high entropy carbide ceramic powder, 25 parts of metal binder phase and 0.8 parts of pyrolytic carbon black. The high entropy carbide powder is added in the form of solid solution (Ti0.8, W0.2) C, WC, NbC, VC, Cr2C3, and the average particle sizes of the above powders are 2.5, 3.0, 1.8, 2.5 and 1.6 microns, respectively, the particle size of iron powder is 2.0 microns, the particle size of cobalt powder is 2.5 microns, and the particle size of carbon black is 0.2 microns.

[0037] The preparation steps of the high entropy carbide-based metal ceramic are as follows: (1) perform the first ball milling, prepare the powder according to the molar ratio of the carbide additive phase, put the powder into a sand mill, the ball-to-material ratio is 15:1, the ball milling time is 2 hours, the ball milling speed is 80r / min, and the grinding medium is anhydrous ethanol. Then, the powder after high-energy grinding is vacuum dried, and after drying, it is vacuum packaged and stored; (2) perform the second ball milling, add iron powder and cobalt powder to the mixed carbide powder, add carbon black; add rubber accounting for 3wt% of the mass fraction of the above powder as a forming agent, and then perform ball milling mixing, the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 8:1, the ball milling time is 48 hours, and the ball milling speed is 80r / min. After ball milling, the mixed powder is spray dried at a drying temperature of 60°C and a particle size of 40 microns; (3) the powder is pressed into a shape at a pressing pressure of 150 MPa; (4) the pressed green body is degreased and sintered to obtain a high entropy carbide-based metal ceramic; the degreasing is carried out in a vacuum environment at a degreasing temperature of 480°C and a degreasing time of 3 hours; the sintering is atmosphere pressure sintering at an atmosphere pressure of 2 MPa; before sintering, the mixture is first heated to 1100°C in a vacuum environment at a vacuum degree of 10 Pa and kept warm for 2 hours, then argon is introduced and atmosphere pressure sintering is carried out at a sintering temperature of 1420°C and an atmosphere pressure of 2 MPa, and kept warm for 1 hour to obtain a high entropy carbide-based metal ceramic material.

[0038] The grain size of the high entropy carbide ceramic is 2.5 microns, its porosity reaches the A02B00C00 level, its bending strength is 2180MPa, and its fracture toughness is 9.2MPa·m 0.5 , Rockwell hardness is 92.1 HRA, and it is a metal ceramic tooling material with wide application potential.

[0039] Comparative Example 1 The other conditions are the same as those in Example 1, except that the added carbide additive phase powder, metal phase powder and graphite powder are directly ball-milled without going through step 1.

[0040] The grain size of the high entropy carbide ceramic is 5.0 microns, its porosity reaches the A06B02C00 level, its bending strength is 1780MPa, and its fracture toughness is 6.8MPa·m 0.5 , Rockwell hardness is 91.0 HRA, which is difficult to meet the industrial demand for tooling products.

[0041] Comparative Example 2 The other conditions were the same as those in Example 2. During vacuum sintering, the temperature was not kept at 1100° C. for 2 h, but was directly raised to 1450° C. for sintering.

[0042] The high entropy carbide ceramic grain size is 2.0 microns, its porosity reaches the A08B00C00 level, its bending strength is 2050MPa, and its fracture toughness is 7.8MPa·m 0.5 , Rockwell hardness is 91.8 HRA. Due to the high oxygen content, the generated gas can no longer be discharged during the pore opening and sintering stage, resulting in a large number of fine pores inside the sintered sample, which makes it difficult to meet the industrial demand for tooling products.

[0043] Comparative Example 3 The other conditions were the same as those in Example 3, except that the atomic ratio of W:Nb:Ti:V:Cr was 1:0.7:1.0:1.0:0.9.

[0044] The high entropy carbide ceramic grain size is 3.5 microns, its porosity reaches the A06B02C00 level, its bending strength is 1980MPa, and its fracture toughness is 7.5MPa·m 0.5 , Rockwell hardness is 91.0 HRA, and no single high-entropy carbide ceramic phase is formed, which makes it difficult to meet the industrial demand for tooling products.

[0045] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.

Claims

1. A method for preparing a high entropy carbide-based cermet, characterized in that: The steps include: Step 1: According to the molar ratio of the carbide additive phase, the powder is prepared and placed in a sand mill for the first ball milling. The ball-to-material ratio is 10-15:1, the ball milling time is 2-5 hours, the ball milling speed is 50-100r / min, and the grinding medium is anhydrous ethanol. The powder after high-energy grinding is then vacuum dried. After drying, it is vacuum packaged and stored; Step 2: Perform a second ball milling, add metal binder, carbon black, paraffin, rubber or polyvinyl alcohol and other binders to the mixed carbide powder, and then perform ball milling. The ball milling medium is anhydrous ethanol, the ball-to-material ratio is 5:1-8:1, the ball milling time is 24-48h, and the ball milling speed is 80-120r / min. After the ball milling, the mixed powder is spray dried at a drying temperature of 50-80°C, and the particle size of the mixed powder is 20-50 microns; Step 3, pressing the powder into a shape with a pressing pressure of 50-200 MPa; Step 4, the green sheet is degreased and sintered to obtain a high entropy carbide-based cermet; the sintering is vacuum sintering or atmosphere pressure sintering, and if vacuum sintering is performed, the vacuum degree is 5-50Pa; if it is atmosphere pressure sintering, the protective gas is argon, and the gas pressure is 0.5-5MPa; the sintering temperature is 1400-1500°C, and the sintering time is 1-3h.

2. The method for preparing a high entropy carbide-based cermet according to claim 1, characterized in that: The carbide is commercial carbide powder, which is composed of at least 4-6 transition metal carbides of TiC, WC, Mo2C, TaC, NbC, ZrC, VC, HfC and Cr2C3; the molar ratio of the metal elements of each added phase is 0.8-1:1-1.2, the ratio difference is ≤20wt%, and the metal bonding phase used is at least one of iron, cobalt and nickel.

3. The method for preparing a high entropy carbide-based cermet according to claim 2, characterized in that: The 4 to 6 transition metal carbides contain at least two phases, TiC and WC.

4. The method for preparing a high entropy carbide-based cermet according to claim 1, characterized in that: The carbide additive phase may be added in the form of simple carbide powder or solid solution powder.

5. The method for preparing a high entropy carbide-based cermet according to claim 1, characterized in that: The molar ratio of the metal elements of each added phase of the carbide is 0.9-1:1-1.

1.

6. The method for preparing a high entropy carbide-based cermet according to claim 1, characterized in that: The average particle size of the commercial carbide powder is 0.5-5.0 microns, the average particle size of the binder phase powder is 1.0-3.0 microns, and the average particle size of the carbon black is 0.1-2.0 microns.

7. The method for preparing a high entropy carbide-based cermet according to claim 1, characterized in that: The content of the metal binder is 15-25wt%, the mass fraction of the carbon black accounts for 0.8-2.0% of the total powder, and the content of the binder such as paraffin, rubber or polyvinyl alcohol accounts for 1.0-3.0wt% of the mass of the metal ceramic powder.

8. The method for preparing a high entropy carbide-based cermet according to claim 1, characterized in that: In step 2, the carbon black is one of colloidal graphite and pyrolytic carbon black.

9. The method for preparing a high entropy carbide-based cermet according to claim 1, characterized in that: In step 4, the degreasing is carried out in a vacuum environment, the degreasing temperature is 300-500° C., and the degreasing time is 2-5 hours.

10. The method for preparing a high entropy carbide-based cermet according to claim 1, characterized in that: In step 4, the sintering process is to first raise the temperature to 1000-1200° C. in a vacuum environment, keep the temperature for 1-3 hours, and then perform vacuum sintering, or introduce argon gas for pressure sintering.

Citation Information

Patent Citations

  • Preparation method for superfine hard alloy

    CN102443714A

  • Ti (C, N) base metal ceramic with homogeneous ring core structure and preparation method thereof

    CN110396632A

  • Ultra-fine grain high-entropy metal ceramic composite material and preparing method thereof

    CN110423930A

  • Ti (C, N)-based metal ceramic with high entropy ring phase structure and preparation method thereof

    CN111850373A

  • High-entropy hard alloy cutter material as well as preparation method and application thereof

    CN115595463A

Cited By

  • Carbide ceramic reinforced hot forging die composite material and preparation method thereof

    CN122327100A